2004
DOI: 10.1111/j.1464-410x.2004.05044.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of haemorrhagic cystitis with sodium pentosan polysulphate

Abstract: OBJECTIVE To assess the use of sodium pentosan polysulphate (SPP) for haemorrhagic cystitis (HC), a potentially life‐threatening side‐effect in patients treated with pelvic radiotherapy or cyclophosphamide, and which can be difficult to manage as patients often have significant comorbidity. PATIENTS AND METHODS Between September 1991 and December 2000, 60 consecutive patients (24 women and 36 men) with haemorrhagic cystitis were primarily treated with SPP; 53 patients had had radical radiotherapy for pelvic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 28 publications
0
34
0
2
Order By: Relevance
“…(Kadrnka, 1981;Marberger et al, 1981;Sanchiz et al, 1996) Sodium pentosan polysulphate Interstitial cystitis, radiation cystitis (Parsons, 1986;Hampson & Woodhouse, 1994;Hwang et al, 1997;Sandhu et al, 2004) Berberine Animal study (Xu & Malave, 2001) N-acetylcysteine Animal study (Palma et al, 1986) Treatment Epsilon-aminocaproic acid Haemorrhage after prostrate resection, cystitis after radiation/chemotherapy (Sharifi et al, 1986;Singh & Laungani, 1992) Sairei-to Radiation/non-radiation cystitis (Shida et al, 1994) Orgotein Radiation cystitis (Kadrnka, 1981;Marberger et al, 1981;Sanchiz et al, 1996) Sodium pentosan polysulphate Interstitial cystitis, radiation cystitis (Parsons, 1986;Hampson & Woodhouse, 1994;Hwang et al, 1997;Sandhu et al, 2004) Nystatin…”
Section: Recommendationmentioning
confidence: 99%
“…(Kadrnka, 1981;Marberger et al, 1981;Sanchiz et al, 1996) Sodium pentosan polysulphate Interstitial cystitis, radiation cystitis (Parsons, 1986;Hampson & Woodhouse, 1994;Hwang et al, 1997;Sandhu et al, 2004) Berberine Animal study (Xu & Malave, 2001) N-acetylcysteine Animal study (Palma et al, 1986) Treatment Epsilon-aminocaproic acid Haemorrhage after prostrate resection, cystitis after radiation/chemotherapy (Sharifi et al, 1986;Singh & Laungani, 1992) Sairei-to Radiation/non-radiation cystitis (Shida et al, 1994) Orgotein Radiation cystitis (Kadrnka, 1981;Marberger et al, 1981;Sanchiz et al, 1996) Sodium pentosan polysulphate Interstitial cystitis, radiation cystitis (Parsons, 1986;Hampson & Woodhouse, 1994;Hwang et al, 1997;Sandhu et al, 2004) Nystatin…”
Section: Recommendationmentioning
confidence: 99%
“…Hampson and Woodhouse 25 reported that 9 of 14 patients with hemorrhagic radiation cystitis achieved control of hematuria after treatment with oral sodium pentosan polysulfate. Sandhu et al 26 also recommended the use of oral sodium pentosan polysulfate as the primary method of managing hemorrhagic cystitis associated with pelvic radiation therapy, based on their experience with 51 patients, of whom 31 responded (21 had their dose reduced to a maintenance dose and 10 stopped treatment). The results were durable after a median follow-up of 450 days (range 19-4,526 days).…”
Section: Pentosan Polysulfatementioning
confidence: 99%
“…Sandhu et al [9] highlighted the potential that SPP has in the management of HC in adult patients. We hypothesised that its effects could be beneficial in paediatric cases of HC.…”
Section: Discussionmentioning
confidence: 98%
“…Its use has dramatically improved outcomes in adults who developed HC secondary to pelvic radiotherapy and cyclophosphamide [9].…”
mentioning
confidence: 99%